Hypertension Unawareness and Uncontrolled among Adults and Elderly People in Rural Communities, Nan Province - Thanakwang, Kattika; Kunnasit, Pimonphan (Journal of Health Science of Thailand, 2018)
This study was aimed at measuring actual prevalence of hypertension and estimating hypertension unawareness and uncontrolled among adults and elderly people dwelling in rural communities. Data used in this study were the secondary data from the 2004 Health Survey in Communities Project of Na Muen district, Nan province. The sample consisted of 3,022 persons aged 35 years and over. Hypertension is defined as a systolic blood pressure ≥ 140 mmHg or diastolic blood pressure ≥ 90 mmHg or reported diagnosis of hypertension. Data were analyzed using descriptive statistics. Results revealed that the prevalence of hypertension was 19.2 percent. When adjusted with persons who reported diagnosis of hypertension, the overall prevalence of hypertension increased to 28.3 percent. Age-specific prevalence of hypertension increased progressively with chronological age. Of all hypertensions, about 43.9 percent were unaware of their high blood pressure, as reported in adults more than the elderly (53.2 % and 31.6 %). However, awareness without treatment or treatment with uncontrollable hypertension were found in 42.7 percent, and prevailed more in the elderly than adults (49.4 % and 36.5 %). These findings suggest that hypertension is highly prevalent in communities, and the rates of awareness and controlled blood pressure are relatively low, indicating an urgent need for developing appropriate programs for screening and health education to prevent and control hypertension in communities.